Second Assessment of Climate Change for the Baltic Sea Basin - BACC II Author Team, The (Cham Springer Nature, 2015)
Earth System Sciences; Atmospheric Sciences; Baltic Sea; Environmental Impacts; Regional Climate Change; Regional Climate Projections
English
Keywords: Environmental economics; Management of specific areas; Physics; Coins, banknotes, medals, seals (numismatics); Earth System Sciences; Atmospheric Sciences; Baltic Sea; Environmental Impacts; Regional Climate Change; Regional Climate Projections